Retail Investor Behavior, Exchanges, and Financial Market Innovation - Insights from the 4th European Retail Investment Conference (ERIC) - Hans-Peter Burghof; Achim Fecker; Carolin Koch; Benedikt Notheisen (Credit and Capital Markets – Kredit und Kapital, 2017)
The 4 th European Retail Investment Conference was hosted at Boerse Stuttgart, Germany, from May 17 th to 19 th 2017. The conference chairs invited academics and practitioners to participate and discuss empirical and theoretical research that investigates retail investor products and services, the impact of technology on retail investors, investors" decision-making, investor protection schemes, and market microstructure. The keynote was given by Prof. David L. Yermack, Albert Fingerhut Professor of Finance & Business Transformation at the Stern School of Business (New York University), Chairman of the Finance Department, and Director of the NYU Pollack Center for Law and Business. – – Privatanleger, Börse und Innovation – Erkenntnisse von der 4. European Retail Investment Conference (ERIC) Vom 17. bis 19. Mai 2017 fand an der Börse Stuttgart die 4. European Retail Investment Conference statt. Die Konferenzteilnehmer aus Wissenschaft und Praxis und diskutierten dabei empirische und theoretische Forschungsarbeiten rund um die Themen Privatanleger und Börsenhandel sowie die Auswirkungen technologischer und regulatorischer Entwicklungen. Die Keynote zum Thema Blockchain wurde von Prof. David L. Yermack, Albert Fingerhut Professor für Finance & Business Transformation an der Stern School of Business (New York University), gehalten.
Keywords: G2; G4; D14; D53; G0; G01; G1; 330; Exchanges; European Retail Investment Conference; Retail Investor Behavior; Financial Market Innovation